(untitled) (Journal of Health Sciences, 2022)
Introduction: The pandemic of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) presented a major challenge to health-care systems around the world. To ensure the continuity of hospital care for patients with cardiovascular diseases, the clinic has formulated the strategy for prevention of transmission of SARS-CoV-2 across the hospital environment. The purpose of this paper is to present the strategy for the prevention of transmission of SARS-CoV-2 in a healthcare facility, using Antigen Rapid Diagnostic Tests (Ag-RDTs).Methods: A description of the work from the hospital committee for the prevention and control of the SARS-CoV-2 epidemic is presented. The hospital has adopted the zero-case strategy. Each positive Ag-RDTs test was sent for confirmation by real-time Reverse Transcription Polymerase Chain Reaction (RT-PCR).Results: During the observed period, 6569 tests were performed at the Magdalena Clinic. Of these, a total of 6100 Ag-RDTs were performed, while 469 were recorded by RT-PCR test. Of these tests, a total of 181 tests showed a positive result, which is a share of 2.75% of all tests performed, of which 144 (2.19%) positive findings were detected among staff. In Ag-RDTs alone, a total of 86 positive people were detected, which is 1.41% of those tested on this type of test.Conclusion: The use of antigen rapid diagnostic tests is an effective and reliable method for the early detection of asymptomatic individuals infected with SARS-CoV-2 in a hospital setting. This strategy can significantly contribute to the insurance of uninterrupted healthcare, providing regular workflow processes, and the care of patients in the safest possible way.